Room Temperature Gas Sensor Based on GaN/PANI Micro Composite with Ultrahigh NH3 Gas Sensibility - LIU Xiaoru; JIA Zhengyang; GUANG Juxu; HAN Dan; SANG Shengbo (Taiyuan Ligong Daxue xuebao)
[Purposes] This study is carriedout to discuss on the response of gallium nitride (GaN) and polyaniline (PANI) composites to ammonia (NH3) at room temperature. [Methods] The GaN micron blocks were prepared by in-situ nitridation by using gallium oxide (Ga2O3) as the raw material, then GaN/PANI gas sensing prototypes were fabricated by in-situ polymerization after pre-composition between GaN and PANI. The samples were characterized. [Findings] It is observed that GaN micron blocks are connected to the mesh-like PANI from morphological result of GaN/PANI gas sensor, and proved the materials are well composited. The experiments are conducted to explore the sensing properties of pure GaN and GaN/PANI. In experimental conditions, the response of GaN/PANI gas sensor to 100×10-6 NH3 is 80.73%, which is 1.7 times that of pure GaN to the same concentration of NH3 and the limit of detection of GaN/PANI is determined to be 1×10-9 while that of pure GaN is 1×10-6 level. The gas sensing mechanism of GaN/PANI sensors is discussed, which provides a theoretical and experimental basis for the development of GaN composition. From this result. The GaN/PANI gas sensor is proved to be an excellent candidate to detect NH3 at room temperature.